Zoo Tycoon 2 - Rymaszewski, Michael (Sybex, 2004)
This practical handbook is certain to assist you in creating a zoo that attracts customers and becomes a profitable enterprise for step-by-step guidance on each phase of your zoo's creation, comprehensive statistics for every aspect of the game, and detailed strategies for keeping the 30+ animals happy and healthy.